The pVHL-hIF-1 system. A key mediator of oxygen homeostasis. - Maxwell, P; Pugh, C; Ratcliffe, P (2001)
Matching oxygen consumption and supply represents a fundamental challenge to multicellular organisms. HIF-1 is a transcription complex which is emerging as a key mediator of oxygen homeostasis. HIF-1 controls the expression of many genes, including erythropoietin, angiogenic growth factors, glucose transporters and glycolytic enzymes. The HIF-1 complex, which contains an alpha and beta subunit (both basic helix-loop-helix proteins of the PAS family) is formed in hypoxia and modulates gene expression through hypoxia response elements. Regulation involves ubiquitin-mediated oxygen-dependent destruction of the alpha subunit. Oxygen-regulated destruction of HIF-alpha requires the von Hippel Lindau tumour suppressor protein (pVHL). pVHL acts as the recognition component of a ubiquitin E3 ligase complex which binds HIF-alpha. Loss of pVHL function, which results in constitutive activation of the hypoxic response, is important in the development of clear cell renal cancer, where both copies of the gene are usually inactivated. The importance of the VHL-HIF system in multicellular organisms is supported by conservation in the nematode C. elegans. Understanding the events resulting in HIF activation should provide novel therapeutic targets. This would be useful in preventing angiogenesis in cancers and promoting adaptive changes in hypoxic/ischaemic tissue.